Clinico‐cytopathologic analysis of 574 Pericardial Effusion Specimens: Application of the international system for reporting serous fluid cytopathology (ISRSFC) and long‐term clinical follow‐up. (7th November 2021) - Song, Min Jeong; Jo, Uiree; Jeong, Ji‐Seon; Cho, Kyung‐Ja; Gong, Gyungyub; Cho, Yong Mee; Song, Joon Seon
Abstract: Introduction: A pericardial effusion (PE) has a variable etiology and the primary role is diagnosis of metastatic malignancy. We analyzed the PE cytology in a large cohort in accordance with the international system for reporting serous fluid cytopathology (ISRSFC) and evaluated the long‐term patient outcomes. Methods: PE specimens from 2010 to 2014 with an available clinical history, cytologic data, and pericardial biopsy results were collected. Results: A total of 574 PE specimens were obtained from 486 patients, representing 1.5% (574/38, 589) of all body fluid specimens. Three hundred and eighty‐two (66.6%) cases were "negative, " 54 (9.4%) cases were "atypia of undetermined significance, " 10 (1.7%) cases were "suspicious for malignancy, " and 128 (22.3%) cases were "malignancy". The most common origin for malignant PE was the lung (82.1%), in both men (70.5%) and women (50.6%). Breast cancer (20%) in women and gastric cancer (4.9%) in men were the second most common malignant PE, respectively. The mean interval from the occurrence of malignant PE to death was 10.06 months (range; 0–116.03 months, median 3.5 months), and the 1‐year survival rate was 16.7%. In addition, the 1‐year survival rates after malignant PE onset were 0% for gastric cancer, 13.9% for lung cancer, 19.8% for breast cancer, and 21.1% for the other cancers ( p  = 0.011). Conclusion: Our present study is the first to our knowledge to classify the pericardial fluid from 574 cases in accordance with the recently published ISRSFC, and to present the long‐term outcomes of patients with malignant PE at the same time. Moreover, we report for the first time that it is gastric and not lung cancer patients that have the poorest prognosis after the occurrence of malignant PE. Abstract : Our study report the long‐term outcomes of patients with malignant pericardial effusion. In addition, most common malignant pericardial effusion was lung cancer and gastric cancer showed the poorest survival prognosis after the occurrence of malignant pericardial effusion.